2018
DOI: 10.19030/jier.v13i2.10101
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Security And Self-Efficacy Among Syrian Refugee Students Inside And Outside The Camps

Abstract: The present study aimed to identify the degree of psychological security and self-efficacy among the Syrian refugee students inside and outside the camps. The sample consisted of 600 students from Syrian refugees inside and outside the camps in the second semester of the academic year 2014-2015. Scales for psychological security and self- efficacy were implemented to answer the study questions. Results indicated low degree of psychological security for Syrian refugee students inside the camps but moderate for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
1
6
0
1
Order By: Relevance
“…Our findings are in line with social cognitive theory that defines self-efficacy as one’s core belief affecting basic processes of personal change (Bandura, 2001 , 2018 ). They are furthermore in line with theoretical considerations of refugee integration that highlight factors of human agency (Echterhoff et al, 2020 ) as well as with research findings in Western (Sheeran et al, 2016 ) and refugee populations (Alharbi, 2017 ; Pak et al, 2022 ) that found similar associations. Accordingly, cross-study evidence indicates that high self-efficacy is associated with a range of positive mental health outcomes among refugees, arguably by bolstering competence beliefs that enable them to manage difficult post-migration stressors in the receiving countries (Echterhoff et al, 2020 ).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our findings are in line with social cognitive theory that defines self-efficacy as one’s core belief affecting basic processes of personal change (Bandura, 2001 , 2018 ). They are furthermore in line with theoretical considerations of refugee integration that highlight factors of human agency (Echterhoff et al, 2020 ) as well as with research findings in Western (Sheeran et al, 2016 ) and refugee populations (Alharbi, 2017 ; Pak et al, 2022 ) that found similar associations. Accordingly, cross-study evidence indicates that high self-efficacy is associated with a range of positive mental health outcomes among refugees, arguably by bolstering competence beliefs that enable them to manage difficult post-migration stressors in the receiving countries (Echterhoff et al, 2020 ).…”
Section: Discussionsupporting
confidence: 84%
“…In Kurdish and Afghan refugees in Australia and New Zealand, lower self-efficacy was associated with lower subjective well-being (Sulaiman-Hill & Thompson, 2013 ). Similarly, an association of higher self-efficacy with more psychological security (Alharbi, 2017 ) and positive affect (Tip et al, 2020 ) was found among Syrian refugees. Moreover, in Syrian refugees in Turkey, self-efficacy was associated with social support and resilience (Pak et al, 2022 ).…”
Section: The Transdiagnostic Approach To Psychopathologymentioning
confidence: 89%
“…A study of 186 Kurdish and Afghan resettled refugees in Australia and New Zealand found that those who scored lower on self-efficacy also reported lower subjective wellbeing, suggesting a positive association between self-efficacy and wellbeing (Sulaiman-Hill and Thompson 2013). Alharbi (2017) found a significant positive relationship between self-efficacy and feelings of psychological security among Syrian refugees in Jordan. Kia-Keating and Ellis (2007) found that higher self-efficacy was associated with fewer depressive symptoms in Somali adolescents who were resettled to the United States.…”
Section: Introductionmentioning
confidence: 84%
“…Alanyazında mülteci öğrencilerin eğitimini temel alan çalışmalara bakıldığında; mülteci öğrencilerin eğitimi ile ilgili merkezlerin yönetiminde (Balkar vd., 2016), eğitim-öğretim ortamlarında (Börü ve Boyacı, 2016), öğrencilerin akademik becerilerinde (Baltacı, 2014;Güngör ve Şenel, 2018;Gömleksiz ve Aslan, 2018), öğrencilerin dili etkin kullanabilmelerinde (Başar vd., 2018;Kuzu vd., 2018), öğretim programı ve içerik uyarlanmasında (Zayimoğlu Öztürk, 2018), öğretmenlerin yaklaşımlarında (Er ve Bayındır, 2015), öğrencilerin uyum sağlama becerilerinin geliştirilmesinde (Mercan vd., 2016;Kiremit vd., 2018) ve kamu politikaları oluşturma süreçlerinde (Özer vd., 2016) çeşitli zorluklar yaşandığı görülmektedir. Diğer taraftan, mülteci öğrencilerin eğitimöğretim sürecine dahil edilmelerinin uyumu kolaylaştırdığı (Croce, 2018), öğrenciler için güven ortamı sağladığı (Boutun, 2016;Alharbi, 2017), marjinalleşmeyi önleyip akran etkileşimini artırdığı (McParker, 2018) ve bunlara bağı olarak da kültürleşme, sosyal adaptasyon ve akademik başarıda olumlu gelişmelerin yaşandığına (Miller vd., 2005) işaret eden çalışmalara da rastlanmaktadır. Mülteci öğrencilerle ilgili yapılan çalışmalar, mülteci öğrencilerin eğitime devam etmelerinin ötesinde, istenen sonuçlara ulaştıracak daha etkili müdahalelere ihtiyaç duyulduğunu göstermektedir.…”
Section: An Examination Of the Teachers' Attitudes Towards The Refugee Students In Terms Of Various Variablesunclassified